Sex-specific differences in the efficacy of renal denervation in patients with resistant hypertension depending on visceral obesity and kidney function - Zyubanova, Irina; Ryumshina, Nadezhda; Mordovin, Victor; Manukyan, Musheg; Lichikaki, Valeriya; Solonskaya, Ekaterina; Gusakova, Anna; Suslova, Tatjana; Pekarskiy, Stanislav; Khunkhinova, Simzhit; Popova, Anastasia; Rudenko, Veronika; et al. (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo investigate the sex differences in the efficacy of renal denervation (RDN) in patients with resistant hypertension (RHT) concerning the size of abdominal fat depots, changes in biomarkers of sympathetic activity, and renal function.Materials and methods24 men (56.5 ± 7.8 years) and 33 women (59.5 ± 8.4 years) with RHT were enrolled in the study and underwent RDN. 24-h ambulatory blood pressure (BP) [systolic/diastolic (SBP/DBP)], serum creatinine (with eGFR calculation), serum adipocytokines (leptin, adiponectin, resistin), serum metanephrines and normetanephrines were measured baseline and 12 months after RDN. The size of subcutaneous, visceral, and perirenal adipose tissue (SAT, VAT, and PRAT) was assessed using MRI.ResultsAfter RDN, BP decreased, leptin increased, and adiponectin, resistin, and metanephrine levels did not change in both sexes. There was a decrease in normetanephrine levels in women and a similar trend in men. In men, the eGFR did not change. In women, the eGFR remained unchanged only in those with chronic kidney disease (CKD) (n = 10) and decreased in the absence of CKD (n = 23) from 79.7 ± 14.1 to 72.1 ± 12.0 ml/min/1.73 m2 (p = 0.011). Men had larger visceral fat depots, and women had larger subcutaneous fat depots. After RDN, the size of adipose tissue in men remained unchanged, and in women, the PRAT thickness decreased from 2.36 ± 1.23 to 2.10 ± 1.17 cm (p = 0.002). Lowering BP in women was associated with increased leptin levels after RDN (r = −0.47 for SBP, r = −0.48 for DBP). Dependence of BP reduction on baseline eGFR was observed in men only [r = 0.44 for SBP, r = 0.48 for pulse pressure (PP)]. Additionally, in men, the decrease in SBP and PP depended on VAT areas (r = −0.44 and r = −0.58, respectively). In women, the SBP reduction showed an inverse correlation between baseline weight (r = −0.35) and waist circumference (r = −0.38).ConclusionsThe magnitude of the antihypertensive effect of RDN depends on signs of visceral obesity and, in men, also on the presence of CKD. Renoprotective effects of RDN in men are obtained regardless of the initial kidney function, while in women, it was observed only in individuals with CKD. Additional beneficial effects of RDN in women include a decrease in normetanephrine levels and a reduction in PRAT size.